2020
DOI: 10.1002/da.22911
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding the impact of complicated grief on combat related posttraumatic stress disorder, guilt, suicide, and functional impairment in a clinical trial of post‐9/11 service members and veterans

Abstract: This is the author manuscript accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…The combination of PTSD and probable PGD also appeared to have a clinical impact, as participants who met criteria for PTSD and probable PGD had higher PTSD symptom severity. This is consistent with previous findings among veterans with combat-related PTSD that those with PGD had greater severity of PTSD (46). SMI clients who have experienced grief and loss may experience particular challenges that may require additional support.…”
Section: Discussionsupporting
confidence: 92%
“…The combination of PTSD and probable PGD also appeared to have a clinical impact, as participants who met criteria for PTSD and probable PGD had higher PTSD symptom severity. This is consistent with previous findings among veterans with combat-related PTSD that those with PGD had greater severity of PTSD (46). SMI clients who have experienced grief and loss may experience particular challenges that may require additional support.…”
Section: Discussionsupporting
confidence: 92%
“…Additional areas of weakness included dropout/withdrawal rates (e.g., less than 60% of participants completed the study, Simon et al, 2020;dropout/withdrawal not reported, Stayton et al, 2019) and study designs without comparison or control groups.…”
Section: Quality Assessment and Risk Of Biasmentioning
confidence: 99%
“…Additional areas of weakness included dropout/withdrawal rates (e.g., less than 60% of participants completed the study, Simon et al, 2020; dropout/withdrawal not reported, Stayton et al, 2019) and study designs without comparison or control groups.…”
Section: Quality Assessment and Risk Of Biasmentioning
confidence: 99%